(untitled) (The Research of Medical Science Review, 2024)
This study examines the prevalence of health anxiety among outpatients receiving care at public and private healthcare facilities in Kabul, Afghanistan. Health anxiety, characterized by excessive worry about health conditions, can significantly impact patients' well-being and their interactions with healthcare providers. Using a cross-sectional survey design, data were collected from a diverse sample of outpatients to assess the levels of health anxiety and its associated factors. The findings indicate a high prevalence of health anxiety within this population, with notable differences observed between public and private healthcare settings. This research highlights the importance of addressing health anxiety in clinical practice and calls for the development of targeted interventions to support affected patients in both public and private healthcare contexts.